Sayyid Qutb’s approach to qur’anic exegesis: an analysis - Ali, Md. Yousuf; Osmani, Noor Mohammad (2015)
Sayyid Qutb (1906-1966) is one of the most influential Islamic scholars in the 20th century who has written many books and articles on Islamic thought in order to relate the Qur’an and Sunnah with integrated approach to modern life. He started a revolutionary mission at a time when Western civilization was at the height of its intellectual, technological, economic and political power, and when almost the entire Muslim world was in the clutches of Western colonial rule. The clouds of gloom were cast upon the Muslims all over the world. In this situation of turmoil, he challenged the spell of Western thought and developed a new ‘Ilm al-Kalam to meet the intellectual challenge of the West. To achieve this goal, in 1948, Qutb began writing to present Islam as the only alternative in every aspect of life in the journal of al-Fikr al-Jadid. His major work is the tafsir fi Zilal al-Qur`an, which is an accumulation of his lifelong experiences and knowledge for modern educated readers. His tafsir is the combination of both al-tafsir bi-al-ma’thur and al-tafsir bi-al-ra’y but some Muslim scholars have alleged that it is as al-tafsir al-siyasi (political tafsir). The aim of this study is, to focus on selected aspects of Qutb’s approach towards understanding the Qur’an in his Qur’anic exegesis. This study evaluates objectively and critically the selected aspects discussed by him to see whether or not he is deviant in his approaches. It also examines whether or not Qutb explains the Qur’an using AÍadith, the views of the companions, asbab al-nuzul, Israiliyyat and other sources. Last but not least, this study also analyses his responses to the theological and philosophical issues, and contemporary Islamic and Western thought.